BS EN 60383-1. Insulators for overhead lines with a nominal voltage above 1000 V. Part 1. Ceramic or glass insulator units for a.c. systems. Definitions, test methods and acceptance criteria (6th December 2019) - British Standards Institution,
No abstract available